2012
DOI: 10.1101/gad.194787.112
|View full text |Cite
|
Sign up to set email alerts
|

Structure and conformational change of a replication protein A heterotrimer bound to ssDNA

Abstract: Replication protein A (RPA) is the main eukaryotic ssDNA-binding protein with essential roles in DNA replication, recombination, and repair. RPA maintains the DNA as single-stranded and also interacts with other DNA-processing proteins, coordinating their assembly and disassembly on DNA. RPA binds to ssDNA in two conformational states with opposing affinities for DNA and proteins. The RPA-protein interactions are compatible with a low DNA affinity state that involves DNA-binding domain A (DBD-A) and DBD-B but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
333
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(349 citation statements)
references
References 42 publications
13
333
2
1
Order By: Relevance
“…These results indicate that HsRPA does not contribute positively or negatively to hMSH2-hMSH6 binding affinity. Moreover, these results confirmed that the displaced ssDNA of the D-loop is unlikely to be encompassed by the bound hMSH2-hMSH6 because the clamp cavity is clearly too small to encompass an HsRPA-bound displaced ssDNA: the dsDNA binding cavity of hMSH2-hMSH6 clamp is 24 Å × 32 Å × 38 Å (11), whereas RPA-ssDNA complex is ∼70 Å × 80 Å × 70 Å (46).…”
Section: Hmsh2-hmsh6 Sliding Clamp Is Constrained Within the D-loop Butsupporting
confidence: 60%
“…These results indicate that HsRPA does not contribute positively or negatively to hMSH2-hMSH6 binding affinity. Moreover, these results confirmed that the displaced ssDNA of the D-loop is unlikely to be encompassed by the bound hMSH2-hMSH6 because the clamp cavity is clearly too small to encompass an HsRPA-bound displaced ssDNA: the dsDNA binding cavity of hMSH2-hMSH6 clamp is 24 Å × 32 Å × 38 Å (11), whereas RPA-ssDNA complex is ∼70 Å × 80 Å × 70 Å (46).…”
Section: Hmsh2-hmsh6 Sliding Clamp Is Constrained Within the D-loop Butsupporting
confidence: 60%
“…HsRPA displays a high affinity 30 nt ssDNA binding mode (29), although structural analysis suggests that only 25 nt are actually bound (23). We found that mismatched DNA containing an oligo-dT 30 ssDNA tail prebound by HsRPA significantly increased the lifetime of HsMSH2-HsMSH6 (τ on = 26.2 ± 1.9 s) compared with unblocked dT 10 or dig-antidig blocked dT 10 (Fig.…”
Section: Significancementioning
confidence: 78%
“…S5). The significant differences in extension when ssDNA is bound by EcSSB compared with HsRPA likely reflects distinct binding mechanisms; whereas the EcSSB tetramer fully wraps ∼65 nt of ssDNA in a "baseball seam" structure (22), HsRPA merely bends ∼30 nt of ssDNA (23). Including EcSSB with HsEXOI completely impeded the contraction of mismatched DNA in the smFS system (Fig.…”
Section: Significancementioning
confidence: 99%
“…Binding involves the ssDNA wrapping around the homotetramer, although bacterial SSBs exhibit considerable variability in their association. In contrast to bacterial SSBs, eukaryotic SSBs generally function as a heterotrimer consisting of six OB folds distributed among three subunits; however, only four of these OB folds are involved in binding to ssDNA (7), which results in an extended arrangement for the protein-ssDNA complex. Telomere end binding proteins, which safeguard the vulnerable telomere 3′ end of ssDNA, also use different numbers of OB folds to bind with ssDNA (8).…”
mentioning
confidence: 99%